2001
DOI: 10.1007/s004380100584
|View full text |Cite
|
Sign up to set email alerts
|

Tagging Hansenula polymorpha genes by random integration of linear DNA fragments (RALF)

Abstract: We have investigated the feasibility of using gene tagging by restriction enzyme-mediated integration (REMI) to isolate mutants in Hansenula polymorpha. A plasmid that cannot replicate in H. polymorpha and contains a dominant zeocin resistance cassette, pREMI-Z, was used as the integrative/mutagenic plasmid. We observed that high transformation efficiency was primarily dependent on the use of linearised pREMI-Z, and that the addition of restriction endonuclease to linearised pREMI-Z prior to transformation inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 29 publications
1
49
0
Order By: Relevance
“…Two Mut Ϫ mutants, designated mpp1-1 and mpp1-2 (previously designated ARJ-59; see Ref. 4), were studied further.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two Mut Ϫ mutants, designated mpp1-1 and mpp1-2 (previously designated ARJ-59; see Ref. 4), were studied further.…”
Section: Methodsmentioning
confidence: 99%
“…The genomic regions of pANL7 and pREMI-59 were initially sequenced using vector-based primers (4). Sequence analysis showed that the pREMI-Z vector had integrated in mutants mpp1-1 and mpp1-2 at two different locations in the same gene that was designated MPP1.…”
Section: Methodsmentioning
confidence: 99%
“…The H. polymorpha strains used in this study are H. polymorpha NCYC 495 (leu1.1; Gleeson and Sudbery, 1988), pex3::URA3 (leu1.1.pex3; Baerends et al, 1996), pex5::URA3 (leu1.1.pex5; Salomons et al, 2000a), and HF295, a DHAS deletion strain (leu1.1.⌬DHAS; van Dijk R. et al, 2001). Yeast cells were grown at 37°C in selective minimal media containing 0.67% yeast nitrogen base without amino acids supplemented with 0.5% glucose (YND) or 0.5% methanol (YNM) or in mineral media (van Dijken et al, 1976) containing 0.25% ammonium sulfate as nitrogen source supplemented with 0.5% glucose, 0.5% methanol, or 0.5% methanol ϩ 0.1% glycerol as carbon sources.…”
Section: Organisms and Growthmentioning
confidence: 99%
“…The H. polymorpha PEX20 gene was identified by RALF mutagenesis (van Dijk et al, 2001). DNA sequencing was performed at Baseclear (Leiden, The Netherlands) using a Licor automated DNA sequencer and dye primer chemistry (LiCor, Lincoln, NB).…”
Section: Isolation and Characterization Of The H Polymorpha Pex20 Genementioning
confidence: 99%